Revisiting the Interplays of Sound, Meaning, Education 23 - edwards, jashen; Rinsema, Rebecca (Critical Studies in Improvisation / Études critiques en improvisation, 2026)
In their editorial for this issue, “Revisiting the Interplays of Sound, Meaning, Education 23,” jashen edwards and Rebecca Rinsema explain: "Drawing upon a range of research methodologies, conceptual framings, and artistic practices, SME 23 nurtured a space for scholarship promoting exploration, curiosity, and dialogue. From improvisational games inviting musical creativity to sonic art integrating experimental electronics, puppetry, and AI visuals; from hearing newly designed musical instruments to listening to local ambience on a semi-guided soundwalk—SME 23 provided multisensory participation. The energy over those three days was infectious. An obvious next step was to engage in another collaboration: between SME and Critical Studies in Improvisation / Études critiques en improvisation."